EFEKTIFITAS PEMBERIAN JUS TOMAT DAN JAMBU BIJI MERAH TERHADAP PENURUNAN KOLESTEROL TOTAL PADA WANITA OVERWEIGHT - Adelina Ayu Nugraheni; Mohammad Jaelani; Arintina Rahayuni; Pujo Semedi (Poltekkes Kemenkes Semarang, 2019)
Background : Women are two times have hypercholesterolemia 14.5% after menopause due to blood cholesterol levels increase because of the hormone estrogen is not formed. Drugs can be used to reduce cholesterol levels, but using drugs to reduce cholesterol levels have side effects. An alternative way that can be used in preventing a long-term increase in blood cholesterol levels and to reduce the dosage of drugs use is by using natural ingredients such as red guava fruit and tomatoes.Objective : This research aim to know the effectiveness of tomato juice and red guava juice on total cholesterol in overweight women.Method : This research was a clinical nutrition research. Type of research was true experiment research and study design was randomized pre-and post-test control group design. The tomato and red guava juice consist of 300 grams of tomatoes and red guavas, was given for 21 days to 22 respondents (11 treatments and 11 controls).In the treatment group there was lowering in total blood cholesterol and the control group with an increase in blood cholesterol levels.Result : Total Blood Cholesterol influenced by the lycopene intake and a decrease in total blood cholesterol levels in the treatment and control groups (p 0.05).Conclusion : 250 ml of tomato juice and red guava juice was given everyday within 3 weeks could reduce total cholesterol 3,01 mg/dl clinically, but not significant statistically.